Analisis Pengaruh Kualitas Layanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Kota Surabaya Pada Platform E-commerce - Oktaviarny, Gabriel Adinda; Nanis Susanti (Cahaya Ilmu Bangsa, 2025)
E-commerce platform is a digital solution that enables online transactions of buying and selling goods and services via the internet. This platform provides a virtual environment for sellers and buyers to interact, offering various features such as product catalogs, shopping carts, payment systems, and shipping tracking. By using the latest technology, E-commerce provides easy accessibility, efficiency, and convenience for users. This study aims to analyze the effect of service quality, trust, and customer satisfaction on customer loyalty to e-commerce platforms in the city of Surabaya. In the implementation of this field research, primary data was taken by distributing questionnaires throughout the city of Surabaya. This research is a quantitative study with a non-probability sampling method and purposive sampling technique. The analysis technique used is path analysis to test the hypothesis, while the classical assumption tests used include, Multicollinearity Test, Heteroscedasticity Test and Normalistic Test. Overall, the indicators used in this study are valid because the correlation coefficient value is> 0.200 with a significance level of <0.05 and are declared reliable because the Cronbach's Alpha coefficient value is> 0.60. The results of the classical assumption test also show that this study has met. The results of this study state that for Model I all variables, namely service quality (X1) and trust (X2) have a significant influence on customer satisfaction (Z) as well as model II all variables, namely service quality (X1), trust (X2) and customer satisfaction (Z) have a significant influence on customer loyalty (Y).